(untitled) ("Conference on Universal Science Research 2023", 2024)
The classification of homonyms is an important aspect of language comprehension and production. Homonyms, including homographs and homophones, can lead to confusion in spelling, pronunciation, and meaning. Understanding the specific features of homonyms is crucial for language learning and developing strong language skills. This article will explore the classification of homonyms and their impact on language comprehension, with a focus on the role of context and vocabulary in disambiguating their meanings. Additionally, the article will discuss the implications of homonyms for linguistics and provide insights into how to effectively navigate and understand these linguistic phenomena.